(untitled) (Contemporary Journal of Social Science Review, 2025)
Ecological crisis is one of the pressing concerns of contemporary age and fiction is the one medium through which ecological concerns can be addressed. This study explores how the depiction of slow violence in Creation Lake, by Rachel Khushner, intensifies environmental injustice. The analysis uses Rob Nixon’s theoretical framework to examine how ecological harm is implemented gradually and bureaucratically, frequently under the guise of legal development. This research analyzes the ways in which the novel’s narrative strategies, and character perspectives expose systemic dispossession, particularly through state-regulated water systems and policy rhetoric, using Catherine Belsey’s method of close textual analysis. It focuses around three fundamental themes, the invisibility and temporal displacement of harm, the complicity of state-corporate systems, and the ability of fiction to make slow violence narratively visible. The findings demonstrate that Creation Lake uses institutional language, deferred causality, and a fractured narrative structure to critique ecological exploitation rather than spectacle. The study affirms the role of fiction in exposing environmental injustice and promoting ecological consciousness where official discourse fails, which aligns with Sustainable Development Goals (SDGs) 6 and 15. It reckons that literature is essential for using narrative and moral witnessing to fight against the normalization of ecological harm.